Psycholinguistic features of political leader speech - Дячук, Н. В. (Studia Philologica, 2019)
Political language has always been an important socio-cultural phenomenon. The article focuses on some psycholinguistic aspects of a political leader speech. Attention is paid to the psycholinguistic methodology of studying aspects of political leader speech peculiarities. The analysis is based on Hillary Clinton’s concession speech. The purposes of the article are to analyze the speech of the American political leader from the point of view of psycholinguistics and characterize the psychological state of the political individual during her speech. It has been established that the speech is characterized by long and complex sentences, which indicates a slight emotionality of the speaker. The vocabulary diversity coefficient is high enough and indicates the richness, diversity and eloquence of the language policy. The verb correlation coefficient indicates a low aggressiveness of the speech, in which gratitude to voters for support and expressing a desire to cooperate with the elected presidential candidate for the sake of the bright future of a common homeland. The logical coherence coefficient indicates a logically structured speech, which is characterized by logic and connectivity. The rate of embolism is extremely low, which indicates the high level of the politician’s speech and the corresponding social status of the speaker. The speech is structured, meaningful, logically connected with the use of appropriate methods of influencing the audience.